Give your child the world : raising globally minded kids one book at a time - Martin, Jamie C. (Grand Rapids, Michigan : Zondervan, 2016)
Six hundred titles that explore the globe are shared in reading lists organized by region, country, and age range.
The world in our homes -- Falling in love with the world -- The good earth: a love story -- Practical ways to invite the world into your home -- The power of story -- Read the world -- The joy of other lands: how to use the reading lists -- Children just like me: multicultural books -- Bring the rain: Africa -- Number the stars: Europe -- The weaving of a dream: Asia -- Silent music: Middle East -- Wagon wheels: North America -- A harvest of hope: Latin America -- Sailing off: Australia, Oceania, and the Polar regions.
Includes index.
Includes bibliographical references and index.
Keywords: Child rearing -- Religious aspects -- Christianity; Parenting -- Religious aspects -- Christianity; Children -- Books and reading; Teenagers -- Books and reading; Children's literature -- History and criticism; Young adult literature -- History and criticism; Books and reading